Huawei - Sarah Alhassan; Dalal Alajmi (AIBPM Publisher, 2019)
Huawei is a leading global provider of information and communications technology which also became the largest Chinese communications equipment manufacturer in the world. Ranked 2010 in the top 500 list.R & D is the main base of the Chinese company, and each year the company dedicates 10% of its sales to this field, and has many centers inside and outside China, all engaged in research and development, and the first external center was opened in this regard was In the Swedish city of Stockholm.In addition to R & D centers around the world, it now has more than 70,000 employees, 45% of its employees working in this sector, and has thousands of patents.